Preparation of poly(DMA-co-DBA) and its application in gene delivery. Issue 1 (2nd January 2023) - Tian, Xiaoxiao; Qiu, Nasha; Shen, Youqing; Zhang, Shizhong; Dang, Chun; Hu, Guang; Wang, Zhihui; Chen, Jing; Ding, Shijie
Abstract: (2-dimethyl amino)ethyl methacrylate (DMA) was co-polymerized with (2-dibutyl amino)ethyl methacrylate (DBA) to form random copolymer P(DMA-co-DBA) with DMA/DBA molar ratios in the range of 9:1 to 1:9 by Atom Transfer Radical Polymerization (ATRP). The (co)polymers were characterized with techniques such as GPC, 1 HNMR and acid-base titration. The cytotoxicity of the polymers was assessed by MTT. Size and zeta potential of P(DMA-co-DBA)/DNA polyplex were analyzed by dynamic light scattering. In vitro gene transfection was performed for P(DMA-co-DBA)/DNA polyplex in the medium with and without serum. In comparison with PDMA/DNA and PEI/DNA, P(DMA-co-DBA) 8:2/DNA showed much higher transfection efficiency than those of PDMA/DNA and PEI/DNA within the range of 0.125 − 1.25 μg·mL −1 of DNA concentrations in the medium with 10% FBS. Confocal images showed that P(DMA-co-DBA) 8:2/DNA was superior to PDMA/DNA and PEI/DNA in the speed and capacity for endosomal release, which might be the main cause of its higher transfection efficiency. Graphical abstract: UF0001